PRESENTATION AND ANALYSIS OF THE STATEMENT OF COMPREHENSIVE IN PERUVIAN COMPANY ADOPT STANDARDS IFRS - Vílchez Olivares, Percy Antonio (2013)
In order to provide useful information to the various users of financial information, such as investors, creditors, lenders, on the results obtained in a given period, various accounting bodies rules issuers of national and international scope in the last two decades have been implemented as part of its provisions required to submit financial information obtained income that have an entity. Additionally, it is important show there are several accounting studies and research that support the usefulness of this information in addition to prepared for general purposes. In the present work of investigation, it analyzed the characteristics of the results comprehensive income, its components, and the IFRS accounting standards on the presentation of the statement of comprehensive income. It also seeks to identify companies that are listed on the Lima Stock Exchange for the period presented results with different amounts Comprehensive results for the period 2011, and on that information to analyze the types of variations that occur between these results, the frequency components of income and expense recognized in equity determinants of comprehensive income, and monetary significance of changes between profit or loss and comprehensive income.